Climate Characteristics of Romang Island - Semuel Laimeheriwa (Faculty of Agriculture, Pattimura University, 2020)
Climate is a very dynamic agriculture production factor and varies according to space and time. Therefore, understanding climate characteristics by analysing and interpreting climate data is the needed in agriculture sector. The objective of the research was to present climate characteristics of Romang Island that are used in the agriculture sector. The climate data was obtained from Rainfall Station of Hila, Climate Station of Lakuwahi, and the Meteorology Station of Saumlaki. Rainfall data was analysed using several methods, namely (1) technique of algebra average, (2) Oldeman equation (1977), (3) Schmidt-Ferguson (1951) and Oldeman (1975) climate classification system; and ( 4) Modified Penman method. The result of data analysis indicated that climate of Romang Island is slightly wet characterized by annual average rainfall of 2.628 mm, with 75% rainfall probability which is equal to 1.794 mm/year. The climate type of Romang Island is B and D1 according to Schmidt-Ferguson and Oldeman classification system, respectively with 11 months of growing season. The highest air temperature is found on November-December and the lowest on months July-August. Humudity is high during the rainy season (December-June) and low during dry season (July-November). While, the sun radiation is longer during dry season and shorter during the rainy season. The annual potential evapotrasnpirasi is 1.771 mm, average wind speed ranges from 1,7 to 4,0 km/hour with the maximum 34 - 58 km/hour. Annually air temperature in this region has been increased as much as 0,0219ºC, while rainfall experiences 5% increasing from period of (1959-1988) to (1989-2018) to the previous period.